2007
DOI: 10.1007/s12055-007-0033-6
|View full text |Cite
|
Sign up to set email alerts
|

Off pump bidirectional Glenn performed through a thoracotomy

Abstract: Introduction:The bidirectional Glenn shunt has become an accepted method of palliation for single ventricle physiology and an intermediate step prior to the Fontan type operations. Attempts have been made to perform this operation without the use of cardiopulmonary bypass thereby eliminating its deleterious effects. The aim of this study was to review our experience with bidirectional Glenn shunt performed via thoracotomy without cardiopulmonary bypass.Methods: Aretrospective review of fifteen patients (11 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Later, Jahangiri et al reported BDG without CPB through a right thoracotomy without using any SVC to RA shunt without any adverse neurological sequelae. Similarly, Dixit et al reported a series of 15 patients operated off‐CPB via a thoracotomy to avoid a re‐sternotomy at the time of Fontan completion. However, the selection criteria in their series were stringent as establishing emergency CPB through this approach is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Jahangiri et al reported BDG without CPB through a right thoracotomy without using any SVC to RA shunt without any adverse neurological sequelae. Similarly, Dixit et al reported a series of 15 patients operated off‐CPB via a thoracotomy to avoid a re‐sternotomy at the time of Fontan completion. However, the selection criteria in their series were stringent as establishing emergency CPB through this approach is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Lamberti polished his research on seven patients in 1990 and after that, there were a series of studies by other authors on off-pump BDG surgery. 1,5,6 Until now, there have been no official reports on this technique in Vietnam.…”
Section: Commentsmentioning
confidence: 99%
“…The bidirectional cavopulmonary connection, also known as the ''bidirectional Glenn'' (BDG) anastomosis, a palliative operation performed in various congenital heart defects with 1 functional ventricle, is usually undertaken via sternotomy with cardiopulmonary bypass. Although there are a few reports of off-pump BDG via thoracotomy access, [1][2][3] to our knowledge a subaxillary approach has never been reported. We describe a case of bidirectional cavopulmonary anastomosis successfully performed through a small right middle subaxillary thoracotomy in an infant with tricuspid atresia in a developing country.…”
mentioning
confidence: 94%